Prime Minister Decrees Nos. : 1159-1160-1161-1162 for the year 2014 On Increasing the fuel Prices = قرارات رئيس مجلس الوزراء أرقام : 1159-1160-1161-1162 لسنة 2014 بشأن أسعار الوقود / Prime Minister. - Egypt. Prime Minister (2025)
Decree of the prime minister no. 1159 of the year 2014 -- Decree of the prime minister no. 1160 of the year 2014 -- Decree of the prime minister no. 1161 of the year 2014 -- Decree of the prime minister no. 1162 of the year 2014 قرار رئيس مجلس الوزراء رقم 1159 لسنة 2014 -- قرار رئيس مجلس الوزراء رقم 1160 لسنة 2014 -- قرار رئيس مجلس الوزراء رقم 1161 لسنة 2014 -- قرار رئيس مجلس الوزراء رقم 1162 لسنة 2014